Males' evolutionary responses to experimental removal of sexual selection. - Pitnick, S. (2001)
We evaluated the influence of pre- and post-copulatory sexual selection upon male reproductive traits in a naturally promiscuous species, Drosophila melanogaster. Sexual selection was removed in two replicate populations through enforced monogamous mating with random mate assignment or retained in polyandrous controls. Monogamous mating eliminates all opportunities for mate competition, mate discrimination, sperm competition, cryptic female choice and, hence, sexual conflict. Levels of divergence between lines in sperm production and male fitness traits were quantified after 38-81 generations of selection. Three a priori predictions were tested: (i) male investment in spermatogenesis will be lower in monogamy-line males due to the absence of sperm competition selection, (ii) due to the evolution of increased male benevolence, the fitness of females paired with monogamy-line males will be higher than that of females paired with control-line males, and (iii) monogamy-line males will exhibit decreased competitive reproductive success relative to control-line males. The first two predictions were supported, whereas the third prediction was not. Monogamy males evolved a smaller body size and the size of their testes and the number of sperm within the testes were disproportionately further reduced. In contrast, the fitness of monogamous males (and their mates) was greater when reproducing in a non-competitive context: females mated once with monogamous males produced offspring at a faster rate and produced a greater total number of surviving progeny than did females mated to control males. The results indicate that sexual selection favours the production of increased numbers of sperm in D. melanogaster and that sexual selection favours some male traits conferring a direct cost to the fecundity of females.